برنامج سكامبر لتنمية مستوى التعرف البصري ومستوى التحليل لدى أطفال الروضة الموهوبين - صبره، رغدة محمد ماهر; الجباس، نبيل السيد حسن; عبدالغني، سلوى عبدالسلام (جامعة المنيا - كلية التربية للطفولة المبكرة, 2022)
هدف البحث الحالي إلى التعرف على تأثير برنامج سكامبر لتنمية مستوى التعرف البصري ومستوى التحليل من مستويات التفكير الهندسي لدى أطفال الروضة الموهوبين، وقد تكونت عينة البحث من 10 أطفال موهوبين من أطفال المستوى الثاني بالروضة (K.G2) قسموا إلى مجموعتين تجريبية وضابطة بعد أن تم ضبط متغيرات الذكاء والعمر والموهبة، وقد قامت الباحثة بتطبيق أدوات قياس مستوى التعرف البصري ومستوى التحليل وهي مقياس مستوى التعرف البصري ومستوى التحليل لدى أطفال الروضة الموهوبين (إعداد الباحثة)، وبرنامج سكامبر لتنمية مستوى التعرف البصري ومستوى التحليل لدى أطفال الروضة الموهوبين (إعداد الباحثة)، والذي يتكون من عشرون نشاط ينمي كل عشرة أنشطة منهم أحد المستويين موضع البحث الحالي، وهما (مستوى التعرف البصري، ومستوى التحليل)، وقد تم تطبيق البرنامج على مدار الأسبوع بواقع ثلاثة إلى أربعة أيام أسبوعيا، وقد انتهى البحث إلى عدد من التوصيات، ومنها ضرورة وعي المعلمات بخصائص أطفال الروضة الموهوبين المختلفة، وتدريبهن على كيفية التعامل معه وفق خصائصه، واستخدام الأنشطة الإثرائية التي تنمي الجانب المتميز فيه الطفل الموهوب، ضرورة الاهتمام بتنمية مستوى التعرف البصري ومستوى التحليل لدى أطفال الروضة سواء العاديين أو ذوي الاحتياجات الخاصة، وقد أظهرت النتائج إجمالا ارتفاع حجم تأثير البرنامج المعد باستخدام استراتيجية سكامبر لتنمية مستوى التعرف البصري ومستوى التحليل لدى أطفال الروضة الموهوبين. The aim of the current research is to identify the effect of the Scamper program to develop the level of visual recognition and the level of analysis- from the levels of engineering thinking- among gifted kindergarten children. Adjusting the variables of intelligence, age, and talent, and the researcher has applied the tools for measuring the level of visual recognition and the level of analysis, which is the measure of the level of visual recognition and the level of analysis for gifted kindergarten children (prepared by the researcher), and the Scamper program for developing the level of visual recognition and the level of analysis for gifted kindergarten children (prepared by the researcher), Which consists of twenty activities that develop each ten activities, including one of the two levels under current research, namely (the level of visual recognition and the level of analysis). The program was applied throughout the week, three to four days per week. Teachers’ awareness of the different characteristics of gifted kindergarten children, training them on how to deal with it according to Its characteristics, and the use of enrichment activities that develop the distinguished aspect of the gifted child The need to pay attention to the development of levels of geometric thinking among kindergarten children, whether normal or those with special needs, and the results have generally shown a high effect of the program prepared using the scamper strategy to develop the level of visual recognition and the level of analysis among gifted kindergarten children.
Keywords: النماذج العلمية -- مستويات التفكير -- التفكير الإبداعي -- رياض الأطفال